The Politics of Food and the Disintegration of the Anglo-Canadian Trade Relationship, 1947-1948 - Muirhead, B. (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 1991)
AbstractThis paper examines a somewhat peripheral event in postwar transatlantic diplomacy, the 1947-48 food negotiations between Canada and the United Kingdom, because the process and the outcome of these talks illuminate the deterioration in the traditionally close relationship between the two countries. Because of the financial strains caused by British wartime expenditures, Canada was unable to negotiate a reestablishment of the prewar trade relationship, in which surpluses in her trade with Great Britain financed deficits in her accounts with the United States. The British negotiating strategy forced the Canadian government to reconsider its traditional dependence on the British connection, which had hitherto been so fundamental to Canadian history. This paper therefore challenges the view that Canadian politicians ''sold out'' the country in shifting attention from Britain to the United States after World War II.